The [U2F12]2− Anion of Sr[U2F12]. Issue 11 (14th February 2018) - Scheibe, Benjamin; Pietzonka, Clemens; Mustonen, Otto; Karppinen, Maarit; Karttunen, Antti J.; Atanasov, Mihail; Neese, Frank; Conrad, Matthias; Kraus, Florian
Abstract: The D 2 h ‐symmetric dinuclear complex anion [U2 F12 ] 2− of pastel green Sr[U2 F12 ] shows a hitherto unknown structural feature: The coordination polyhedra around the U atoms are edge‐linked monocapped trigonal prisms, the U V atoms are therefore seven‐coordinated. This leads to a U–U distance of 3.8913(6) Å. A weak U V –U V interaction is observed for the dinuclear [U2 F12 ] 2− complex and described by the antiferromagnetic exchange J exp of circa −29.9 cm −1 . The crystalline compound can be easily prepared from SrF2 and β‐UF5 in anhydrous hydrogen fluoride (aHF) at room temperature. It was studied by means of single crystal X‐ray diffraction, IR, Raman and UV/VIS spectroscopy, magnetic measurements, and by molecular as well as by solid‐state quantum chemical calculations. Abstract : Stuck on U : Sr[U2 F12 ] is synthesized. It contains the D 2 h symmetric [U2 F12 ] 2− anion, which is the first example of a dinuclear fluoridouranate(V) complex. The spectroscopic and magnetic properties could be reproduced by quantum chemical calculations. An antiferromagnetic coupling of the U V atoms is observed.